Передумови і хід молдавського походу Сулеймана Кануні 1538 р. та його наслідки для прикордонного становища Буковини - Балух, О. (Чорноморська минувшина, 2021)
У статті проаналізовано військово-політичне становище північномолдавських земель (Буковини) у 30-х рр. XVI ст. протягом польсько-молдавських військових конфліктів та посилення османської експансії у Центрально-Східній Європі. Під час боротьби між Польщею та Молдавією за Покуття, яке межувало з територією Буковини, правитель Османської імперії, домовившись із поляками, вирішує скинути непокірного господаря Петру Рареша та загарбати всю країну. Наслідком потрапляння держави у васальну залежність від Османської імперії в 1538 р. стало погіршення воєнно- політичного становища буковинських земель, які опинилися на передовій боротьби між Портою та Польщею. The territory in Upper Suceava, Siret, Upper Popruttia and Middle Podnistrovya (Bukovyna) played an important part in international relations due to transcontinental trade routes connecting the north of Western Europe and the Black Sea. Moreover, it was a confluence of political and economic interests of current major countries of Central and Eastern Europe, mostly Poland and later Ottoman Empire which had been competing for the hegemony in the region and craved to be decisive in its history. During 1530, the Ottoman Empire and Poland wanted to extend their power to Moldavia and to Bukovina. The reason for this was that the region was at the forefront of the struggle between both countries. Frontier conflicts between Poland and Moldavia lasted until 1538 when Turkish sultan and Polish king arranged Tartar Horde to capture Moldavian lands and Polish troops which surrounded Khotyn fortress forced Petru Rares make a vassal oath to Zygmunt I. Still it did not help preserve Moldavian sovereignty as Turkish sultan occupied Suceava due to Moldavian boyars betrayal, while Petru Rares was compelled to escape to Transylvania. Thus, Moldavia and the territory of Bukovyna went over to Ottoman Empire, which had negative consequences on the situation of the local people, restricting its agricultural and demographic development. The borders of Bukovyna became, therefore, the borders of Ottoman Empire. Besides, eastern part of Bukovyna (with the centre in Khotyn) was subordinate to Turkish administration which created an important defense point that often became the location for battles in coming years. Thus, after the Moldavian state became dependent on the Ottoman state in 1538, the situation in Bukovynian lands deteriorated significantly. The consequence of this was that from the end of the XVI – the beginning of the XVII century Bukovyna was the object of military-political competition, and power over the region passed from hand to hand.